The Influence of Learning Style on Learning Outcomes of Students of The Economics Department Faculty of Economics State University of Medan - Angela Priska; Maya Duita Saragih; Shidiq Fathanah; Senin Apdi Serep Jeremiah Tampubolon; Jusmanromualdiharion Sinaga; Dionisius Sihombing (Outline Publisher, 2025)
This study aims to determine the effect of learning styles on the learning outcomes of students of the Department of Economics, Faculty of Economics, State University of Medan. The study used a quantitative method with a causal associative approach. The sample of the study was 30 students selected purposively. Data were obtained through a questionnaire to measure learning styles (visual, auditory, kinesthetic) and documentation of the Cumulative Achievement Index (IPK) as a learning outcome. Simple linear regression analysis was used to determine the relationship between variables. The results showed that learning styles did not have a significant effect on student learning outcomes. The F test produced F count 0.390 < F table 3.93 with a significance of 0.538 > ( 0.05), and the coefficient of determination (R-square) value of 0.014 indicated that learning styles only explained 1.4% of learning outcomes, while 98.6% was influenced by other factors. This study confirms that although learning styles are important, learning outcomes are more determined by other factors that need to be explored further.